Detection of Immunoglobulin M Antibodies to P35 Antigen of Toxoplasma gondii for Serodiagnosis of Recently Acquired Infection in Pregnant Women - Suzuki, Yasuhiro (American Society for Microbiology, 2000)
We examined the efficiency of detection of immunoglobulin M (IgM) antibodies to a 35-kDa antigen (P35) of Toxoplasma gondii for serodiagnosis of acute infection in pregnant women. A double-sandwich enzyme-linked immunosorbent assay (ELISA) with recombinant P35 antigen (P35-IgM-ELISA) was used for this purpose. On the basis of the clinical history and the combination of results from the toxoplasma serological profile (Sabin-Feldman dye test, conventional IgM and IgA ELISAs, and the differential agglutination test), the patients were classified into three groups: group I, status suggestive of recently acquired infection; group II, status suggestive of infection acquired in the distant past; group III, status suggestive of persisting IgM antibodies. Eighteen (90.0%) of 20 serum samples from group I patients were positive by the P35-IgM-ELISA, whereas none of the 33 serum samples from group II patients were positive. Only 4 (25.0%) of 16 serum samples from group III patients were positive by the P35-IgM-ELISA, whereas all these serum samples were positive by the conventional IgM ELISA. These results indicate that demonstration of IgM antibodies against P35 by the P35-IgM-ELISA is more specific for the acute stage of the infection than demonstration of IgM antibodies by the ELISA that uses a whole-lysate antigen preparation. Studies with sera obtained from four pregnant women who seroconverted (IgG and IgM antibodies) during pregnancy revealed that two of them became negative by the P35-IgM-ELISA between 4 and 6 months after seroconversion, whereas the conventional IgM ELISA titers remained highly positive. The P35-IgM-ELISA appears to be useful for differentiating recently acquired infection from those acquired in the distant past in pregnant women.